Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.2174/156720208786413415
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Alcohol Consumption on Neurotransmitters -An Overview

Abstract: Alcohol one of the important products of the global addiction alters brain function by interacting with multiple neurotransmitter systems, thereby disrupting the delicate balance between inhibitory and excitatory neurotransmitters. Alcohol positively reinforces drinking by producing a mild euphoria. The reinforcing effects of alcohol are mediated by several neurochemical systems and are associated with some of the behavioral manifestations of intoxication. Alcohol consumption is initially accompanied by decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 0 publications
0
31
0
1
Order By: Relevance
“…Glycine accomplishes several functions as a transmitter in the CNS (3). Though the patients with alcoholic liver disease showed reduced concentrations of plasma glycine level in one study (14), our study showed that the plasma glycine level reduced insignificantly in ALD subjects compared to the control group, but significantly in NAFLD subjects compared to other two groups (Table1).…”
Section: Amino Acids In Liver Diseasesmentioning
confidence: 55%
See 1 more Smart Citation
“…Glycine accomplishes several functions as a transmitter in the CNS (3). Though the patients with alcoholic liver disease showed reduced concentrations of plasma glycine level in one study (14), our study showed that the plasma glycine level reduced insignificantly in ALD subjects compared to the control group, but significantly in NAFLD subjects compared to other two groups (Table1).…”
Section: Amino Acids In Liver Diseasesmentioning
confidence: 55%
“…In addition, alcohol is linked to categories of disease whose relative impact on the global burden is predicted to increase (1). Chronic heavy drinking and alcoholism can have serious consequences for the functioning of the entire nervous system, particularly the brain (2) by interacting with multiple neurotransmitter systems, and thereby disrupting the delicate balance between inhibitory and excitatory neurotransmitters (3). At the cellular level, alcohol appears to affect brain function, primarily by interfering with the action of glutamate, gamma-aminobutyric acid (GABA) and other neurotransmitters (2).…”
Section: Introductionmentioning
confidence: 99%
“…How proinflammatory cytokines modulate neuronal activity is just beginning to be elucidated. It has been suggested that proinflammatory mediators may facilitate the activation of GABA A receptors [4]. Indeed an interaction between TLR4 and GABA A-α2 has recently been demonstrated, although in this case knockdown of GABA A-α2 in the central nucleus of the amygdala led to a reduction in TLR4 expression, with the reverse situation not examined [19].…”
Section: Role Of Tlrs In Mediating the Acute Cns Effects Of Alcoholmentioning
confidence: 84%
“…This shift in balance is to compensate for the depressant effect of alcohol. 21,22 One of the comorbid factors of chronic alcohol use is social anxiety disorder. 23 Chronic alcohol intake leads to a decrease in the level of striatal dopamine in rats and dopamine D 2 receptors in humans.…”
Section: Discussionmentioning
confidence: 99%